Migrant's health needs in receiving countries from a bio-psycho-social approach - Angela Yánez Corrales; Laura Andrea de la Fuente Flores; María Cecilia Toffoletto; María Patricia Masalan Apip (Medisur)
At present, the Chilean government is making an effort to guarantee the new citizens their rights, with different costumes and in general with a different life style. Therefore, it is of great relevance to know their social, biological and psychological needs through the experience in the receiving countries to make optimum health management in the country. The objective of this work is to analyze the treatment to the health needs of migrants in receiving countries regarding a bio-psycho-social approach of the integrated model set in Chile. The analysis of health needs was organized according to the centrality of the bio-psycho-social model and the information was organized regarding the above mentioned needs. It is concluded that the main needs are related to sexual and reproductive health, infectious contagious, chronic degenerative and cardiovascular diseases and feeding disturbances.